2004
DOI: 10.1513/pats.2306013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Claudins in Determining Paracellular Charge Selectivity

Abstract: Tight junctions create regulated barriers in the paracellular space between epithelial cells, including those of the airway and alveolus. Junctions vary widely throughout the body in their electrical resistance and, to some extent, in their ionic charge selectivity. Paracellular differences complement transcellular transport to define overall water, ion, and solute movements. A large family of transmembrane proteins called claudins has recently been implicated in creating the variable properties of the junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 39 publications
2
46
0
Order By: Relevance
“…The charge-selective property of the tight junction could be demonstrated by P Na , P Cl , and their ratio (27,31,57). Normally, the paracellular channels in the small intestine intrinsically favored positively charged molecules and ions, i.e., high P Na /P Cl ratio (24,57), as confirmed by P Na /P Cl of 2.4 and 3.7 in the duodenum and Caco-2 monolayer, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The charge-selective property of the tight junction could be demonstrated by P Na , P Cl , and their ratio (27,31,57). Normally, the paracellular channels in the small intestine intrinsically favored positively charged molecules and ions, i.e., high P Na /P Cl ratio (24,57), as confirmed by P Na /P Cl of 2.4 and 3.7 in the duodenum and Caco-2 monolayer, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Since PRL stimulated the paracellular calcium transport in both duodenal epithelium and Caco-2 monolayer, we determined the epithelial charge selectivity, which was known to influence transport of several ions through the paracellular pathway (19,57). In the duodenum, 800 ng/ml PRL increased P Na /P Cl from a control value of 2.40 Ϯ 0.06 (n ϭ 8) to 3.16 Ϯ 0.23 (n ϭ 8, P Ͻ 0.01; Fig.…”
Section: Prl Altered Charge Selectivity In Duodenum and Caco-2 Monolayermentioning
confidence: 99%
“…45,46 Their localization and both intracellular and intercellular interactions are postulated to form pores that regulate paracellular movement of ions. 47,48 Absent or faulty claudin-16 activity could therefore prevent the reabsorption of Mg 2ϩ (as well as Ca 2ϩ ) and result in FHHNC. Consistent with this hypothesis is the recent observation that a similar phenotype is observed in individuals with mutations in claudin-19, which is also located at the tight junction of the TAL.…”
Section: Mgmentioning
confidence: 99%
“…Both types of junctions have been shown to exist in alveolar epithelium of lung, but there is no detailed knowledge of their function, and even their distribution in normal and diseased human lung is poorly understood. The tight junctions vary in the different epithelia, and they are often divided into leaky and tight types (Van Itallie and Anderson 2004). Less than a decade ago, it was observed that claudins are the main family of proteins that make up the tight junctions (Tsukita et al 2001).…”
mentioning
confidence: 99%